Período de incubación y generación de Hemileia vastratix Berk Br en Honduras - Tronconi, N.M.=700 1 Palma, M.R.; Suazo, G.; Zaldívar, R.; Agurcia, R.D.
Sumario (Es)
Ilus.; 5 ref.
Keywords: COFFEA ARABICA; ROYA; HEMILEIA VASTATRIX; HONDURAS